Have you heard of Rift Valley fever? Findings from a multi-country study in East and Central Africa - Raymond Odinoh; Jeanette Dawa; Silvia Situma; Luke Nyakarahuka; Luciana Lepore; Veerle Vanlerberghe; Carolyne Nasimiyu; Sheila Makiala; Christian Ifufa; Daniel Mukadi; Herve Viala; Nicholas Owor; et al. (PLoS ONE, 2025)
Introduction Rift Valley Fever (RVF) has caused several outbreaks across Africa, impacting human health and animal trade. Recent reports indicate sporadic detections of RVF virus among humans and animals in East Africa during inter-epidemic periods. We assessed RVF knowledge levels in East and Central Africa across countries with different epidemiological profiles. Materials and Methods Individuals aged ≥10 years with acute febrile illness were enrolled from six health facilities in Kenya, Uganda, and the Democratic Republic of Congo (DRC). Sociodemographic information was collected, and participants were asked questions regarding their knowledge of RVF transmission, symptoms, prevention, and control. Blood samples were tested for anti-RVF antibodies (IgG and IgM). Knowledge was categorized as absent, basic, or advanced. Descriptive and ordinal logistic regression analysis identified factors associated with RVF knowledge. Results Among 4,806 participants (median age 31, IQR 22–44, 57.5% female), only 20.5% had knowledge of RVF (16.4% basic, 4.1% advanced). Knowledge levels varied by country: DRC (3.1%), Uganda (16.1%), and Kenya (42.6%). RVF seropositivity was 10.4% in Uganda, with much lower rates in Kenya (2.0%) and DRC (1.5%). Factors associated with RVF knowledge included age 21–40 years (aOR 2.03; 95%CI 1,55–2.67) and >40 years (aOR 2.51; 95%CI 1.88–3.37), male gender (aOR 1.44; 95%CI 1.20–1.73), profession as a healthcare worker (aOR 5.63; 95%CI 3.48–9.12), residence in Kenya (aOR 26.8; 95%CI 15.8–48.4) or Uganda (aOR 5.43;95%CI 3.19–9.79), completing primary education (aOR 3.89; 95%CI 2.18–7.52) with advanced (postgraduate) education shown to increase knowledge, (aOR 22.8; 95%CI 4.95–18.6). Other factors included presence of livestock within the homes (aOR 1.26; 95%CI 1.01–1.57) and use of methods to prevent mosquito bites (aOR 1.62; 95%CI 1.32–1.98). Animal farmers, butchers, and those with close animal contact showed no association, despite being at-risk populations. Conclusion Overall RVF knowledge was low across the study sites, with the highest levels observed in Kenya, moderate levels in Uganda despite greater exposure, and markedly low levels in the DRC. Targeted risk communication is urgently needed for high-risk populations in all regions particularly in Uganda, where elevated exposure contrasts with limited knowledge. Increased awareness is crucial for high-exposure groups in all regions, particularly in Uganda where exposure is higher, but knowledge remains relatively low.